Tribology of Insitu Zn-Al/ZrB2 Composites in Reciprocating Motion - Kumar V.; Gautam G.; Mohan A.; Mohan S. (My University, 2025)
This work presents tribological characteristics of Zinc-Aluminum (Zn-Al) alloy and ZrB2 particles reinforced composites in reciprocating motion under dry conditions. Zn-Al alloy composites with 3, 6, and 9 vol% of ZrB2 particles were fabricated via in-situ stir casting route using resistance-heated muffle furnace. Reciprocating wear tests were conducted on all compositions using Multifunctional Tribometer in a range of 10 N–55 N load and sliding speed of 0.075 m/s–0.300 m/s. Results were analyzed for coefficient of friction and wear. Tools such as scanning electron microscope for texture and profilometer for surface roughness were used to analyze relaxed layer of all compositions to understand tribological phenomena. Significant improvement was seen with increased amount of hard ZrB2 particles in tribological properties. © 2022, American Foundry Society.